Development of Low-Resistance Coastal Stow Net Using Numerical Analysis and Model Experiments - Sua Park; Jihoon Lee; Minseo Park; Daeyeon Cho (Fishes)
In coastal stow net fishing, the heavy weight of a typical anchor (750–1000 kg) can increase the risk of capsizing the boat and crew member injury during hoisting operations. Thus, to prevent these accidents, a reduction in the anchor weight is required. One strategy to achieve this is to reduce the resistance force of the fishing gear used, which would allow lighter anchors to be employed. This requires the accurate estimation of the resistance force for various gear designs. Therefore, the resistance force and shape during the operation of two representative types of coastal stow nets currently employed in the Korean coastal stow net fishing industry were investigated using simulations and modeling experiments. The modeled fishing gear was divided into four sections according to the mesh size. Based on the results, the twine thickness was reduced in order to target areas of the gear where the greatest resistance was observed, while the front part of the gear was redesigned to prevent the front of the net from being pushed back into a suboptimal shape. The proposed low-resistance fishing gear has the potential to improve occupational safety in the coastal stow net fishing industry.